The Effect of Working Capital and Company Size on Profitability in Industrial Sector Companies on the IDX (2020–2024) - Herdi Herdian Apriansyah; Dani Sopian (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of working capital and company size on profitability in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Profitability is an important indicator in assessing a company's financial performance because it reflects the company's ability to generate profits from the resources it has. This study uses descriptive and verifiable methods with a quantitative approach. The research population includes all industrial sector companies listed on the IDX, with purposive sampling techniques, so that 39 companies were obtained as samples. With an observation period of five years, the number of data analyzed was 195 observations. The research data is obtained from the company's officially published annual financial statements. Data analysis was carried out using statistical methods to test the influence of independent variables on dependent variables. The results show that working capital does not always have a positive effect on the company's profitability, which indicates that high working capital is not necessarily followed by efficient asset management. Meanwhile, the size of the company has a role in reflecting the stability and operational capacity of the company, although its effect on profitability depends on the effectiveness of management. This research is expected to contribute to the management of companies and investors in financial decision-making.